Praktik Jurnalisme Konstruktif Pada Isu Dinasti Politik Di Pilkada 2020 (Analisis Framing Model Robert N Entman Dalam Berita Pilkada 2020 di CNN Periode 10-17 Desember 2020) - Soraya, Iin; Putra, Jaqualine Pramanta; Syarief, Fauzi; Alif, M. Ismail (Jurnal Komunikasi, 2021)
: Regional Head Elections held simultaneously in various regions in Indonesia. In 2020, the 2020 regional elections will take place on December 9, postponed from the original schedule due to the corona pandemic. However, the names of those who registered as candidates for regional leaders who have emerged are thought to have had kinship ties to state officials. Therefore it is necessary to control the press / media, in providing and making journalistic products that are in accordance with the performance, behavior and integrity of the pilkada participants. So for this reason, this study is intended to identify and describe the news frame using Robert N Entman's framing analysis as a constructive analytical model and to frame how constructive journalism practices in the issue of political discipline in the 2020 Pilkada at cnnindonesia.com. Meanwhile, the purpose of conducting this research is to describe the frame on the news of political dynasty issues on cnnindonesia.com. and To describe the practice of journalism in framing news on issues of political dynasties at cnnindonesia.com. The result of this research is the process of searching and gathering this news by browsing and searching on the web www.cnnindonesia.com, the core research intends to see the practice of constructive journalism in the news frame in the 2020 elections in reporting on issues of political dynasties. Converting on whether the news applies ethics in cover both side writing, by looking at the use of words and sentences that can make a negative indication in the 2020 elections.